The Future of NCES's Longitudinal Student Surveys - John Robert Warren (SAGE Publishing, 2015)
The National Center for Education Statistics' (NCES) longitudinal student surveys have long been exceptionally useful for many purpose. Despite their many virtues, however, these surveys cannot be used to monitor trends at short time intervals, they do not allow for flexible changes to survey content, they cannot generally be used to infer policy effects, they are not useful for international comparisons, and they are of limited value to local stakeholders. NCES should consider doing to its longitudinal students surveys what the Census Bureau did to the decennial census long form and what NORC has long done for the General Social Survey: Move to annual rotating panels and allow outside investigators to field (and fund) supplemental topical modules. NCES should also continue to work with the research community to explore new survey content areas and modes of observation, improve the quality of spatial measures, and pursue record linkage to administrative data.